Perceived Risk Attitudes: Relating Risk Perception to Risky Choice - Weber, Elke U.; Milliman, Richard A. (Management Science, 1997)
This paper provides empirical evidence that distinguishes between alternative conceptualizations of the risky decision making process. Two studies investigate whether cross-situational differences in choice behavior should be interpreted in the expected utility framework as differences in risk attitude (as measured by risk-averse vs. risk-seeking utility functions) or as differences in the perception of the relative riskiness of choice alternatives as permitted by risk-return interpretations of utility functions, leaving open the possibility of stable cross-situational risk preference as a personality trait. To this end, we propose a way of assessing a person's inherent risk preference that factors out individual and situational differences in risk perception. We document that a definition of risk aversion and risk seeking as the preference for options perceived to be more risky or less risky, respectively, provides the cross-situational stability to a person's risk preference that has eluded more traditional definitions. In Experiment 1, commuters changed their preferences for trains with risky arrival times when the alternatives involved gains in commuting time rather than losses. However, changes in preference coincided with changes in the perception of the riskiness of the choice alternatives, leaving the perceived risk attitudes of a majority of commuters unchanged. Experiment 2, a stockmarket investment task, investigated changes in risk perception, information acquisition, and stock selection as a function of outcome feedback. Investors' stock selections and their perception of the risk of the same stocks were different in a series of decisions in which they lost money than in a series in which they made money. As in Experiment 1, differences in choice and in risk perception were systematically related, such that the majority of investors had the same preference for perceived risk in both series of decisions. Our results provide empirical support for the usefulness of recent risk-return conceptualizations of risky choice (Bell [Bell, D. E. 1995. Risk, return, and utility. Management Sci. 41 23–30.], Jia and Dyer [Jia, J., J. S. Dyer. 1994. A standard measure of risk and risk-value models. Working paper, University of Texas at Austin.], M. Weber and Sarin 1993).